Innovative management processes at the industrial enterprise - E P Nazarenkov (RUDN Journal of Engineering Research, 2010)
The author analyzed combination of traditional specific structures and forms of management. The analysis also involves methods of problems solving for innovative management processes at the industrial enterprise.